THE ROLE OF GOVERNMENT SUPPORT FOR INNOVATION AND PERFORMANCE OF SMEs - Nungky Viana Feranita; Alifian Nugraha; Sampir Andrean Sukoco (Universitas Muhammadiyah Jember, 2020)
This study inspect and analyzes the impact of government support on SME performance both directly and indirectly through innovation. The sample in this study was 165 SMEs in East Java which focused on several regencies / cities which were the eastern development corridor area and had a distinctive superior food and beverage business. The collected data is then analyzed using path analysis. Of the four hypotheses proposed in this study, all were accepted. The results of testing the hypothesis of direct influence indicate that government support influences the performance of SMEs, government support influences SMEs innovation, and innovation influences the performance of SMEs. The results of hypothesis testing indirect effects indicate that government support influences the performance of SMEs through innovation.